Rectene Isocrates sophistis nonnumquam adnumeretur - Danek, Zbigniew (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The article addresses the question whether it is a proper opinion to consider Isocrates a sophist as many commentators claim. In his analysis the author refers to the passages in which the rhetor expresses his negative judgments about the opinions and actions performed by the sophists. The author examines also the circumstances in which Isocrates defends the members of this movement, as he finds it a beneficial way to protect also himself from many false and malicious statements. In conclusion, Isocrates is considered to have a unique status as a sophist and to be a philosopher who aspires to the role of the spiritual leader of the Greeks of that time.